2015
DOI: 10.1038/cr.2015.69
|View full text |Cite
|
Sign up to set email alerts
|

Angiomotin binding-induced activation of Merlin/NF2 in the Hippo pathway

Abstract: The tumor suppressor Merlin/NF2 functions upstream of the core Hippo pathway kinases Lats1/2 and Mst1/2, as well as the nuclear E3 ubiquitin ligase CRL4DCAF1. Numerous mutations of Merlin have been identified in Neurofibromatosis type 2 and other cancer patients. Despite more than two decades of research, the upstream regulator of Merlin in the Hippo pathway remains unknown. Here we show by high-resolution crystal structures that the Lats1/2-binding site on the Merlin FERM domain is physically blocked by Merli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
183
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(194 citation statements)
references
References 62 publications
10
183
1
Order By: Relevance
“…Although AMOT can induce LATS2-mediated phosphorylation of YAP and sequester YAP/TAZ to tight junctions (Chan et al, 2011; Paramasivam et al, 2011; Wang et al, 2011; Zhao et al, 2010a), AMOT is also reported to activate YAP by binding YAP in the cytoplasm to prevent LATS1/2-mediated phosphorylation and to promote transcription (Yi et al, 2013). Moreover, AMOT binds to and activates NF2 (Li et al, 2015). Here, in response to serum starvation, the AMOT KO cells were slightly more sensitive but overall did not show much difference from the wild-type cells.…”
Section: Resultsmentioning
confidence: 99%
“…Although AMOT can induce LATS2-mediated phosphorylation of YAP and sequester YAP/TAZ to tight junctions (Chan et al, 2011; Paramasivam et al, 2011; Wang et al, 2011; Zhao et al, 2010a), AMOT is also reported to activate YAP by binding YAP in the cytoplasm to prevent LATS1/2-mediated phosphorylation and to promote transcription (Yi et al, 2013). Moreover, AMOT binds to and activates NF2 (Li et al, 2015). Here, in response to serum starvation, the AMOT KO cells were slightly more sensitive but overall did not show much difference from the wild-type cells.…”
Section: Resultsmentioning
confidence: 99%
“…For example, we show in this study that USH1C binds to site 5 in F3 and site 6 formed by the F1/F2/F3 interface of Myo7b C-terminal FERM domain. In a number of FERM domain proteins with auto-inhibitory tails, each tail is known to simultaneously bind to sites 3 and 4 in the F3 and F2 lobes, respectively (31,47,48). The Crumbs tail is shown to simultaneous bind to site 1 in the F3-lobe and site 2 in the F1/F3 interface (49).…”
Section: Discussionmentioning
confidence: 99%
“…Motins have also been implicated in a feed-forward loop that promotes Hippo pathway activation: Motins are substrates of LATS [83-86], and phosphorylation by LATS both stabilizes Motins, and promotes their binding to Merlin. Binding of Motins to Merlin appears to influence Merlin conformation, such that its binding to LATS is enhanced, which presumably promotes further LATS activation [87]. …”
Section: Dynamic Localization Of Hippo Pathway Componentsmentioning
confidence: 99%